An impact of type 2 diabetes mellitus on NKT-like cell population in humans: a new insight into impaired immune response in hyperglycemia - Adamska-Fita, Emilia; Śliwka, Przemysław Wiktor; Stasiak, Bartłomiej; Karbownik-Lewińska, Małgorzata; Lewiński, Andrzej; Stasiak, Magdalena (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by insulin resistance and pancreatic β-cell dysfunction. T2DM is associated with increased risk of infections and of several malignancies, although the underlying immune mechanisms remain not fully elucidated. Natural Killer T-like cells (NKT-like) belong to a unique subpopulation of T lymphocytes defined by expression of the markers specific to NK (Natural Killer) cells (CD56) and T cells (TCR - T cell receptor). As NKT-like cells possess unique cytotoxic properties, they form a bridge between innate and adaptive immunity. The aim of our study was to assess associations between the presence of T2DM and the profile of NKT-like cell subpopulations.MethodsPeripheral blood mononuclear cells (PBMCs) were obtained from 86 patients. NKT-like cells were subsequently isolated from the PBMC fraction using a CD3+ CD56+ NKT cell isolation kit in combination with magnetic bead-based separation. To evaluate NKT-like cells subpopulations distribution, flow cytometry (FC) was used. NKT-like cells were categorized into CD4-CD8- (double negative, DN), CD4+CD8-, CD4-CD8+, and CD4+CD8+ (double positive, DP) subpopulations, with further subdivision of DP and CD4-CD8+ subpopulations into CD4highCD8mid/CD4midCD8high and CD4-CD8mid/CD4-CD8high subpopulations, respectively. Associations between NKT-like cells subpopulation and T2DM, and – additionally – correlations between NKT-like and glucose levels and body mass index (BMI) were evaluated.ResultsT2DM group demonstrated a significantly diminished percentage of DN NKT-like cells as compared to control group. A strong negative correlation was observed between DN NKT-like cell levels and glucose concentration, but not BMI. Based on further subdivision of DP and CD4-CD8+ subpopulations a significant negative correlation was also observed between glucose levels and the CD4-CD8mid NKT-like cell subpopulation. No such association was detected for the other subpopulations.ConclusionsOur study demonstrated that DN NKT-like cells, which possess significant cytotoxic activity, are depleted in T2DM patients. These results may explain the novel potential mechanism of increasing susceptibility to infections and cancers in T2DM and emphasize the need for precise glycemic control. The novel insights into NKT-like cell immunomodulation role in T2DM may open new, targeted therapies in metabolic diseases. Further research in larger cohorts is needed to confirm these pioneering observations.